Pengaruh Upah, Pertumbuhan Ekonomi, dan Inflasi Terhadap Pengangguran Di Indonesia - Ihsanul Fikri; Ali Anis (Jurnal Kajian Ekonomi dan Pembangunan, 2023)
The purpose of this research is to find out and analyze how wages, economic growth and inflation affect unemployment in Indonesia. The research data was obtained from secondary data, namely data from the Indonesian Central Bureau of Statistics. The dependent variable in this study is unemployment while the independent variables consist of wages, economic growth and inflation. The analysis used in this study is panel data regression analysis by applying the Random Effect Model (REM) method. The results of the study show that wages have a negative and significant effect on unemployment in Indonesia, while economic growth and inflation have a negative and insignificant effect on unemployment in Indonesia.